Metabolic link between auxin production and specialized metabolites in Sorghum bicolor. (27th October 2022) - Perez, Veronica C; Dai, Ru; Tomiczek, Breanna; Mendoza, Jorrel; Wolf, Emily S A; Grenning, Alexander; Vermerris, Wilfred; Block, Anna K; Kim, Jeongim
Abstract: Aldoximes are amino acid derivatives that serve as intermediates for numerous specialized metabolites including cyanogenic glycosides, glucosinolates, and auxins. Aldoxime formation is mainly catalyzed by cytochrome P450 monooxygenases of the 79 family (CYP79s) that can have broad or narrow substrate specificity. Except for SbCYP79A1, aldoxime biosynthetic enzymes in the cereal sorghum ( Sorghum bicolor ) have not been characterized. This study identified nine CYP79-encoding genes in the genome of sorghum. A phylogenetic analysis of CYP79 showed that SbCYP79A61 formed a subclade with maize ZmCYP79A61, previously characterized to be involved in aldoxime biosynthesis. Functional characterization of this sorghum enzyme using transient expression in Nicotiana benthamiana and stable overexpression in Arabidopsis thaliana revealed that SbCYP79A61 catalyzes the production of phenylacetaldoxime (PAOx) from phenylalanine but, unlike the maize enzyme, displays no detectable activity against tryptophan. Additionally, targeted metabolite analysis after stable isotope feeding assays revealed that PAOx can serve as a precursor of phenylacetic acid (PAA) in sorghum and identified benzyl cyanide as an intermediate of PAOx-derived PAA biosynthesis in both sorghum and maize. Taken together, our results demonstrate that SbCYP79A61 produces PAOx in sorghum and may serve in the biosynthesis of other nitrogen-containing phenylalanine-derived metabolites involved in mediating biotic and abiotic stresses. Abstract : Identification of an enzyme in sorghum for phenylacetaldoxime (PAOx) production reveals a link between auxin metabolism and defense metabolite production in monocots, which may contribute to a growth–defense trade-off.